Solid state interfacial reaction of Sn–37Pb and Sn–3.5Ag solders with Ni–P under bump metallization - He, Min (2012)
Thermal aging is one of the accelerated tests for IC package reliability during manufacturing processes and under actual usage conditions. During the process of thermal aging, intermetallic compounds (IMC) grow continuously due to element diffusion, resulting in their morphology change and thickness increase. In this work, the solid state reaction between electroless Ni–P and two types of Sn-based solders (Sn–3.5Ag and Sn–37Pb) has been investigated. Three distinctive layers, Ni3Sn4, NiSnP and Ni3P, were found between the Sn-containing solders and Ni–P under bump metallization. The growth rates of Ni3Sn4 IMC at different temperatures were obtained from the aged samples and the activation energy of Ni3Sn4 growth was estimated. The kinetic data obtained show that the Ni3Sn4 in the Sn–3.5Ag/Ni–P joints grows much faster than with the Sn–37Pb solder under the same condition. Kirkendall voids are found inside the Ni3P layer after thermal aging. The void formation mechanism is due to net Ni out-flux into the solder area.